MOSS SOFTWARE: A NEW TOOL FOR MULTI-OBJECTIVE GREEN SUPPLIER SELECTION - Toktas-Palut, Peral; Onan, Kıvanç; Zahid Gürbüz, Mustafa; Gülden-Özdemir, Birsen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Competition between companies is getting more intense by the day. Corporations need to decrease costs while improving the quality and reliability of their deliveries. Meanwhile, the demand for environmentally sustainable products and operations is increasing. These issues are all compounded by the supplier relations between companies and their need to develop better economic and environmental supply chain contracts. This research thus aims to propose a tool, i.e., the MOSS Software, concerning the total cost, rate of defected materials, rate of late deliveries, and environmental improvement potential for suppliers. MOSS is a two-stage software. First, the objectives are included in a multi-objective evolutionary mathematical model, and the model is solved using the NSGA-III algorithm. In the second stage, as a post-Pareto analysis approach, the k-means algorithm is used for selecting representative solutions among Pareto sets by comparing silhouette values for different k values. An application of the MOSS software is also presented in this paper.